Threshold concepts in religious studies: A qualitative and theoretical exploration of threshold concepts in a "nodal" curriculum. - Mosurinjohn, Sharday C. (Teaching Theology & Religion, 2021)
This article explores "threshold concepts" in North American religious studies undergraduate education. The threshold concepts approach concentrates on how certain concepts or learning experiences can act like the threshold of a doorway that opens onto a new perspective for the learner. Crucially, they come into play in learning to think like a professional within a discipline. Little work has been done on threshold concepts in religious studies. In this article I explore what threshold concepts might be central to it. I also distinguish religious studies as a "nodal" discipline, in contrast to "sequential" ones, and describe how threshold concepts function in a nodal curriculum differently than they do in a sequential one. Drawing on the Scholarship of Teaching and Learning literature, plus my own focus group data from religious studies faculty and students, I argue that the threshold concepts approach is useful for religious studies professors examining what concepts should be at the heart of our curricula and what it means to "think like a religious studies scholar."